2019
DOI: 10.1111/jac.12361
|View full text |Cite
|
Sign up to set email alerts
|

Potential involvement of rapeseed (Brassica napus L.) metallothioneins in the hydrogen peroxide‐induced regulation of seed vigour

Abstract: Germination is a crucial process in crop plant life cycle that determines future yield. Hydrogen peroxide plays a significant role in both dormancy release and seed ageing. The potential of the rapeseed metallothioneins (BnMT1‐4) as reactive oxygen species scavengers was investigated. In the presence of H2O2, bacterial cells expressing BnMT1‐4 had higher growth rate than control cells. However, such effect was not observed in an oxidative stress oversensitive yap‐1Δ yeast mutant strain expressing BnMT1‐4. Next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…The expression of MTs genes is also changed in plants inoculated with bacteria that promote their growth, which is confirmed by the research of Hrynkiewicz et al [48]. In contrast, in oil palm (Elaeis guineensis), the expression of type-3 MT increased in roots and leaves as a result of inoculation with the pathogenic fungus Ganoderma bininense and the symbiotic fungus Trichoderma harzianum [30]. Research by Voiblet et al [57] showed that MT expression was downregulated in Eucalypus globus in the presence of the fungus Pisolithus tinctorius.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The expression of MTs genes is also changed in plants inoculated with bacteria that promote their growth, which is confirmed by the research of Hrynkiewicz et al [48]. In contrast, in oil palm (Elaeis guineensis), the expression of type-3 MT increased in roots and leaves as a result of inoculation with the pathogenic fungus Ganoderma bininense and the symbiotic fungus Trichoderma harzianum [30]. Research by Voiblet et al [57] showed that MT expression was downregulated in Eucalypus globus in the presence of the fungus Pisolithus tinctorius.…”
Section: Discussionmentioning
confidence: 56%
“…One example is the induction of expression by MT1, MT2, and MT3 in B. rapa [68]. Research by Mierek-Adamska et al [30] showed that BnMT1-BnMT4 in rapeseed perform an antioxidant function when they are over-expressed in bacteria. Under stress conditions, plants activate additional processes to allow survival, with genes encoding oxidative enzymes and MTs being expressed [69].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior cDNA synthesis from 1 µg of RNA genomic DNA was removed using RNAse free DNase I (Thermo Fisher Scientific, Waltham, MA, USA). Further oligo(dT) 18 primer and RevertAid reverse transcriptase (Thermo Fisher Scientific, Waltham, MA, USA) were used for cDNA synthesis, in accordance with the protocol described in [84].…”
Section: Expression Analysis Of Bnrsh Genesmentioning
confidence: 99%